Mineral Nitrogen in Soil of Sugarcane Plantation of PG Jatiroto - Wijaya, Ketut Anom (UNEJ e-Proceeding, 2014)
The objective of research was to study mineral N content in soil of PG Jatiroto sugarcane plantation, Lumajang, East Jawa. Mineral N of soil is very important data in utilizing the precise N fertilization method. Rate based fertilization had been discontinuedly utilized by some advanced countries since 1980s because it was considered to be environmentally unfriendly, not appropriate for precision agriculture which oriented toward inner quality.Â  In the future, Indonesia is also expected to implement the method of accurate N supply on sugarcane to replace the rate based method. Nitrate and ammonium content in soil analized using Cataldo method andÂ  Conway Dish method. Soil samples were taken on two kind of soil texture (sandy soil and loamy soil). Result: content of mineral nitrogen in soil of sugarcane plantation was unexpected extrimly high (2.000-10.000 kg/ha) compare to nitrogen need of sugarcane for yielding highest sugar content (around 350 kg N/ha), nitrate-Nitrogen in general, was very much lower (20-150 kg/ha) than ammonium-Nitrogen (2.500-9.800 kg/ha). Conclusion: mineral N in soil of sugarcane plantation of PG Jatiroto extrimly high and much higher than need of N of sugarcane to produce high sugar content, ammonium-N was the majority of mineral N form in both of soil types.. Keywords: sugar plantation, soil, nitrogen-mineral, nitrate, ammonium